Reinterpreting the Dana Dance of Jambi's Arab-Malay Community in the Creation of Rentak Bedana - Dony Osmond (Pascasarjana Institut Seni Indonesia Padang Panjang, 2025)
Reinterpretations of traditional dance through new choreography often emphasize formal transformation, while the means of retaining the social spontaneity of participatory dance within a structured composition remain underexplored. This artistic research examines the transformation of elements of the Dana dance of Jambi’s Arab-Malay community into Rentak Bedana and analyzes its artistic outcomes in movement, interaction, performance structure, music, and visual design. The creative process comprised exploration, improvisation, composition, and rehearsal. Materials were generated through observation of Dana dance characteristics, review of visual documentation and literature, movement experiments with six dancers over approximately six months, creative notes, rehearsal evaluations, photographic documentation, and observation of the performance. The data were analyzed reflectively by examining relationships among ideas, movement motifs, spatial patterns, music, expression, and the cultural identity of the source tradition. The findings show that dynamic and communicative movement, a joyful communal atmosphere, and spontaneity can be transformed through variations in space, time, energy, floor patterns, and movement-music relations within a three-part structure. Controlled spontaneity allows dancers to vary accents, duration, gaze, and qualities of response to the music and other dancers, while remaining within the source motifs, atmosphere, spatial boundaries, section duration, and predetermined choreographic meeting points. The study’s novelty lies in formulating controlled spontaneity as a strategy that connects the participatory character of Dana dance with the demands of a choreography that can be rehearsed and repeated without eliminating individual responsiveness. This formulation offers a practical framework for tradition-based dance creation. However, because the analysis concerns a single work and relies on the creator’s documentation and internal evaluation, Rentak Bedana should be regarded as a potential model of traditional development rather than evidence of successful preservation; assessment by the source community and audience reception remains necessary